Reproductive potential of the black bean aphid (Aphis fabae Scop.) on a range of faba bean (Vicia faba L.) accessions - Henrik Skovgård; Frederick L. Stoddard (Legume Science, 2023)
Abstract The black bean aphid is one of the main insect pests of faba bean, leading to yield losses in many countries. The aphid inflicts damage to faba bean through direct phloem feeding and indirectly by transmission of several viruses. Sources of genetic resistance or tolerance to the aphid have been hard to identify and to use in breeding because of the high environmental variability of the attack, the weak and partial nature of the resistance when found, and the low repeatability of experiments. A range of molecular genotyping tools is now available for identifying the genes underlying key traits in faba bean. Hence, we screened the responses of eight inbred lines (Columbo, Albus, Closed‐flower, Diana, Hedin/2, Icarus, ILB938/2, and Mélodie/2) of faba bean, derived from commercial cultivars and experimental germplasm, to aphid infestation in controlled (no‐choice‐test) and field (preference test) conditions. In the controlled environment, aphid performance was assessed by measuring fecundity and determining the intrinsic rate of natural increase (rm). In the field experiment, population growth was examined on Columbo, Closed‐flower, Hedin/2, and ILB938/2 during June and July. Each week, 10 plants in each plot, randomly chosen at the start, were screened for aphid colonization and number of plants attacked. For each plant, an index number was given reflecting the severity of aphid presence. Our results demonstrate a clear conformity between the results obtained from the indoor pot experiments and the field experiments. In both experiments, ILB938/2 showed partial resistance with significantly lower fecundity, rm, and field infestation when compared with the known susceptible line Columbo. The consistently strong performance of ILB938/2 against the black bean aphid suggests that it carries a factor or factors rendering it unconducive to aphid landing, feeding, and/or reproduction. Further investigation into the resistance mechanisms of ILB938/2 is planned.